Membangun Generasi Qur’ani melalui Pendidik yang Berintegrasi: Strategi Pendidikan Anak Usia Dini Berbasis Al Quran dan Hadits - Izzatul Iffah; Evi Rahayu; Syafruddin Syafruddin; Zulheldi Zulheldi; Rehani Rehani (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood education is a critical phase in shaping the spiritual and moral foundations that will determine the quality of future generations. In the context of Islamic early childhood education institutions, the integration of Qur’anic and Prophetic values in learning activities is still insufficient, and the role of educators as primary models in forming Qur’anic character has not been fully optimized. This study aims to formulate Qur’an- and Hadith-based early childhood learning strategies through the concept of the “integrated educator,” namely an educator who is able to unify knowledge, exemplary character, and spiritual practice within the educational process. This research employed the library research method through an in-depth review of tafsir works, Islamic education literature, recent scientific articles, and early childhood education regulations. The findings reveal that the formation of a Qur’anic generation can be achieved through five core strategies: prophetic role modeling, integrating Qur’anic values into daily routines, contextual habituation of worship, the use of storytelling methods (Qur’anic and prophetic narratives), and strengthening emotional–spiritual intelligence based on hadith. The novelty of this study lies in the formulation of the conceptual model of the “Qur’anic integrated educator,” which combines pedagogical, spiritual, and prophetic approaches simultaneously as a strategic framework to enhance the quality of Qur’an- and Hadith-based early childhood education